Acceptance Level of Islamic Banking Products and Services: A Case Study of Peshawar, Pakistan - Ullah, Naqeeb (2023)
This study explores the consumer acceptance of Islamic banking products and services (IBP&S) in Peshawar, Pakistan, considering the moderating role of religious motivation. The deductive approach is employed, utilizing awareness of IBP&S, understanding of Islamic banking products and services, socio-political factors, and the 4Ps of marketing as independent variables. The dependent variable is customer acceptance of Islamic banking, and Bank Alfalah Islamic, Bank Islami Pakistan, MCB Islamic Bank, Soneri Mustaqeem Islamic Bank, and HBL Islamic Bank are considered. Data from 400 clients were collected through primary sources with verbal consent. The findings reveal that awareness, knowledge and socio-political factors of Islamic banking products and services have an insignificant effect on consumer acceptance.However, the 4Ps of marketing significantly influence customer acceptance. Religious motivation does not significantly moderate the relationships. The study concludes that consumer acceptances are influenced by various factors, and marketing plays a crucial role in enhancing customer satisfaction and the adoption of Islamic banking services. The lack of awareness and the presence of alternative choices affect the adoption rate. Future research should conduct in-depth interviews for further analysis. Islamic banks should focus on marketing practices, profitability, community service, unique services, and religion to attract customers. Policymakers in Pakistan should consider the cultural, economic, and social factors that impact banking service adoption,customizing measures to suit Peshawar's unique characteristics and increase residents'comfort in using financial services. Policy implications highlight the importance of policymakers understanding the cultural and social aspects that influence the adoption of banking services. Further research can help policymakers customize measures for Peshawar's urban environment, facilitating increased comfort and usage of financial services among its residents